Energy efficiency in building an analysis study of K-Value and U-Value application through green building material / Anas Zafirol Abdullah Halim ... [et al.] - Abdullah Halim, Anas Zafirol; Talkis, Nor Azizah; Wan Ali, Wan Nordiana; Majid, Mohd Fareh (Universiti Teknologi MARA, Perak, 2022)
The increasing energy consumption can have a long term effect in building. If it is not well managed, it can lead to a huge impact especially on costs due to energy wastage. There will be various problems when the use of energy efficiency is ignored, among them are wasteful use of energy in buildings from unplanned energy consumption costs, increase the cost of electricity thus giving a high impact on the cost of services. Most of the designers often ignore the basic requirements in building design, particularly in the selection of construction materials that do not suit with the local climate. Building always received a lot of heat because the construction of the wall surface do not use environmentally friendly materials which can absorb heat during the day. Therefore the objective of this research is to investigate alternative building materials as environmentally friendly building materials that can prevent the entry of high intensity heat into the building. This research is done through the study of k-value and U-Value of the material. This research is conducted by using The Hilton B480 Thermal Conductivity of Building & Insulating Materials Unit equipment based on International Standard for Steady State Measurement, ISO8301. From this study, it is found that Brickool is a new alternative to green building material that is environmentally friendly and able to give an impact on the use of energy efficiency in building. Brickool has low thermal conductivity and a high insulation rate when compared with other conventional building materials.